PERAN PROFESIONALISME GURU MENGHAPAPI TANTANGAN ERA GLOBALISASI: Teachers are professional, and the era ofglobalization - Harwanto, Harwanto (Buana Pendidikan, 2011)
Teachers are professional teachers capable of acting as the architect of the transformation of the nation through science and technology, build character of children to moral and personality, improve skills and psychomotor skills and instill emotional stability and noble. Teachers are expected to take part in the midst of situations that are modern (inovative and creative), unique (different and new), and advanced (smelling science and technology telecommunication and practical). In the era of globalization, the teacher must be able to create ideas, solve problems (solution), building the image and determine management options through the process of learning, education and development of students.